Sosialisasi Penggunaan Aplikasi Blended Learning Sebagai Penunjang Pembelajaran Daring Di Masa Pandemi Covid-19 - Hardianto, Roki; Fajrizal; Musfawati (FLEKSIBEL: Jurnal Pengabdian Masyarakat, 2021)
Community Service raised the title "Socialization of the Use of Blended Learning Applications to Support Online Learning during the Covid-19 Pandemic". The activity was carried out because the rules regarding online learning from home had been decided since the Covid-19 pandemic broke out in Indonesia. Students and lecturers in the teaching and learning process interact using e-learning applications. The goal is that all activities can be stored as university archives for accreditation and other purposes. At the Lancang Kuning University the e-learning application is called blended learning. Community Service Activities were held at the Zoom Meeting with the aim of preventing the transmission of Covid-19. At the event, 89 students attended the Zoom Meeting from the Faculty of Computer Science. The implementation of activities is carried out for one day with a discussion of the use of blended learning material in the form of account registration, class management to the teaching and learning process in the blended learning application. This activity has outputs, namely the PKM journal that has been published in the OJS online journal, news of activities published scientifically and useful knowledge for participants.